(3GdebOeI GdLRQjIs - (3GdTjQGRj, GdYeQj, CHh GdNjQ, GHf GdLRQj, TeS GdOjf, eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa (B((3, J (B833 (3g`(B)s
(3ChdgG (B:s
(3jbhd QGLj Yah QH SGeY(B***(3eMeO Hf GdLRQj GdTGaYs
(3BNQgG (B:s
(3CHjGJgG bGa hRGj aj GdYOO(B***(3ef jJbf GdJLhjO jXaQ HGdQTOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7/45s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdbQGAGJ hGdJLhjOs